EXOCYTOSIS OF LATEX BEADS DURING THE ENCYSTMENT OF ACANTHAMOEBA - Stewart, James R. (The Rockefeller University Press, 1972)

(untitled)
Cells of Acanthamoeba castellanii (Neff) are known to form mature cysts characterized by a cellulose-containing cell wall when transferred to a nonnutrient medium. Amebas which engulfed latex beads before encystment formed mature cysts essentially devoid of bead material. The encystment of bead-containing cells appeared to be similar to that of control cells since no important differences between the two were observed with respect to cellular levels of glycogen or protein, cellulose synthetase activity, the amount of cyst wall polysaccharide formed, or the percentage of cysts formed. Actinomycin D and cycloheximide inhibited encystment as well as bead expulsion. Ultrastructural analysis revealed that the beads, which initially were contained in phagocytic vesicles, were released from the cell by fusion of vesicular membranes with the plasma membrane. Exocytosis was observed in cells after 3 hr of encystment, with most of the beads being lost before cyst wall formation. Each bead-containing vesicle involved in expulsion was conspicuously demarcated by an area of concentrated cytoplasm, which was more homogeneously granular than the surrounding cytoplasm. Beads were not observed in the cytoplasm of mature cysts but were occasionally found in the cyst wall.